STUDENTS’ PERCEPTION ON THE USE OF GROUP DISCUSSION IN SPEAKING CLASS AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Stya Mayasari Sardjono (PBI 15 UMY 047, 2015)
*47 Group discussion is one of the techniques in the learning process. Based on the researcher experience group discussion it has almost been implemented in every class at English Education Department of Universitas Muhammadiyah Yogyakarta. This research is aimed at knowing the perception advantages and disadvantages of using group discussion in speaking class at EED of UMY. This research used descriptive qualitative as the research design. It was conducted at EED of UMY. As research participants; the researcher chose six students from batch 2014 based on criteria. The criteria were made based on the students’ GPA level. In addition, the students must have engaged into listening and speaking for formal setting class and listening and speaking for daily conversation class. The instrument used is in-depth interview. In analyzing the data, this research used open coding, axial coding, and selective coding. Before coding, the researcher had checked the validity of the data by doing member checking. The finding of the study includes the advantages and disadvantages of using group discussion in speaking class. Based on students’ perception group discussion to deliver opinion, to improve speaking, to increase self confident, to add knowledge, to make student relax and understand more about the material, to understand new vocabulary, to work cooperatively, to socialize with other students, to solve problem, and to create an interesting learning process. In contrast, the disadvantages of group discussion revealed by student English x Education Department UMY involve group discussion does not facilitate passive student; it causes different argument among group members; monitoring students is difficult to be done by teacher; student’ opportunity to express opinions is very limited. To conclude, this research showed that students at EED of UMY felt that group discussion could give many advantages toward their learning. In contrast, some students also felt that group discussion bring disadvantages toward their learning.